Proceedings of the 11th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2019
DOI: 10.1145/3342197.3344523
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Patterns in Pedestrian Interaction with Vehicles

Abstract: In road-crossing situations involving negotiation with approaching vehicles, pedestrians need to take into account the behavior of the car before making a decision. To investigate the kind of information about the car that pedestrians seek, and the places where do they look for it, we conducted an eye-tracking study with 26 participants and analyzed the fixation behavior when interacting with a manually-driven vehicle that approached while slowing and displaying a yielding behavior. Results show that a clear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…The eye-tracking results showed that the Windscreen eHMI yielded a concentrated gaze pattern, which can be explained by the fact that this eHMI is embedded in the centre of the car. This finding is in line with Dey et al [36], who showed that pedestrians are inclined to look at the windscreen when an oncoming car gets close to the pedestrian. The Wheels eHMI also yielded a concentrated gaze pattern, but only for a brief period of about 1 s before the car came to a full stop.…”
Section: Eye-trackingsupporting
confidence: 91%
See 1 more Smart Citation
“…The eye-tracking results showed that the Windscreen eHMI yielded a concentrated gaze pattern, which can be explained by the fact that this eHMI is embedded in the centre of the car. This finding is in line with Dey et al [36], who showed that pedestrians are inclined to look at the windscreen when an oncoming car gets close to the pedestrian. The Wheels eHMI also yielded a concentrated gaze pattern, but only for a brief period of about 1 s before the car came to a full stop.…”
Section: Eye-trackingsupporting
confidence: 91%
“…Even though research (e.g., [35]) shows that pedestrians and drivers do not make direct eye contact very often, an eye-tracking study by Dey et al [36] showed that pedestrians tend to look at the windscreen when an approaching car is close by, "likely to seek the intention or information about the situational awareness of the driver" (p. 375). Accordingly, a windscreen-based eHMI may be an attractive location for presenting a message.…”
mentioning
confidence: 99%
“…This study aimed to explore which parameters affect pedestrians' understanding of the FAV's intentions as expressed in crossing decisions of participants on fixed crossing scenes, as well as the change of crossing decisions over time (learnability). Results revealed that pedestrians fixated on the FAV's e-HMI, in line with previous research (Dey et al, 2019;Eisma et al, 2020). But, unlike what has been suggested in a previous study (Holländer and Butz, 2019), pedestrians do not always base their decision on the e-HMI proposition as demonstrated through the e-HMI background color, or message type -instruction or status.…”
Section: Discussionsupporting
confidence: 85%
“…Explicitly, it can indicate whether pedestrians looked at the e-HMI and for how long before the decision to cross or not. Field research investigated pedestrians' gaze patterns, but only with a manual car that did not include e-HMI (Dey et al, 2019). Another research reported a negative correlation between pedestrians' subjective understanding of the FAV intention and their gaze fixation duration (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that pedestrians mostly look at the ground, street edges, and other persons and vehicles (Fotios, Uttley, Cheal, & Hara, 2015;Simpson, Freeth, Simpson, & Thwaites, 2019), but these studies do not report results regarding interactions with moving cars. In an experiment using a manually-driven vehicle that approached while slowing down, Dey, Walker, Martens, and Terken (2019) found that pedestrians were inclined to look at the windshield when the car was close by, perhaps to read the driver's face or seek eye contact. Whether these findings can be generalised to more complex traffic conditions remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%